2016
DOI: 10.7287/peerj.preprints.2403v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing evolutionary timescales using phylogenomics

Abstract: Reconstructing the timescale of the Tree of Life is one of the principal aims of evolutionary biology. This has been greatly aided by the development of the molecular clock, which enables evolutionary timescales to be estimated from genetic data. In recent years, high-throughput sequencing technology has led to an increase in the feasibility and availability of genome-scale data sets. These represent a rich source of biological information, but they also bring a set of analytical challenges. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The choice has been described as “often subjective” (Ho and Duchêne, 2014, p. 5949) and “notoriously difficult to quantify” (Klopfstein, 2021). Choosing priors “could be considered a dark art” (De Baets et al., 2016) and errors “can lead to highly unreliable estimates of evolutionary timescales” (Tong et al., 2016). Carruthers and Scotland (2021) concluded that: “uncertainty about the relationship between fossil ages and clade ages [i.e.…”
Section: Methodological Problems In the Chronological Analysis Of Evo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice has been described as “often subjective” (Ho and Duchêne, 2014, p. 5949) and “notoriously difficult to quantify” (Klopfstein, 2021). Choosing priors “could be considered a dark art” (De Baets et al., 2016) and errors “can lead to highly unreliable estimates of evolutionary timescales” (Tong et al., 2016). Carruthers and Scotland (2021) concluded that: “uncertainty about the relationship between fossil ages and clade ages [i.e.…”
Section: Methodological Problems In the Chronological Analysis Of Evo...mentioning
confidence: 99%
“…The choice has been described as "often subjective" (Ho and Duchêne, 2014, p. 5949) and "notoriously difficult to quantify" (Klopfstein, 2021). Choosing priors "could be considered a dark art" (De Baets et al, 2016) and errors "can lead to highly unreliable estimates of evolutionary timescales" (Tong et al, 2016) Scotland (2021) concluded that: "uncertainty about the relationship between fossil ages and clade ages [i.e. the priors] is often such that it is difficult to meaningfully implement fossil calibrations"; Spasojevic et al (2021) observed that "although largely arbitrary, these settings [the priors] determine the outcome of any nodedating analysis".…”
Section: Methodological Problems In the Chronological Analysis Of Evo...mentioning
confidence: 99%
“…The morphology of these led Engel & Grimaldi (2004) and Grimaldi & Engel (2005) to interpret this specimen as a possible flying insect. Subsequently, R. hirsti has commonly been used to calibrate molecular clocks (e.g., Warnock, Yang & Donoghue, 2011; Misof et al, 2014; Wolfe et al, 2016) or to suggest that insects have first appeared in the Silurian (e.g., Grimaldi, 2010; Nel et al, 2013; Tong, Lo & Ho, 2016). Yet other authors have expressed doubts about the insect affinities of the specimen (e.g., Rasnitsyn & Quicke, 2002) and suggested that it could also represent a myriapod.…”
Section: Introductionmentioning
confidence: 99%